2001
DOI: 10.1074/jbc.c100346200
|View full text |Cite
|
Sign up to set email alerts
|

A New Member of the Family of Di-iron Carboxylate Proteins

Abstract: Ubiquinone (UQ) is an essential cofactor for respiratory metabolism. In yeast, mutation of the COQ7 gene results in the absence of UQ biosynthesis and demonstrates a role for this gene in the step leading to the hydroxylation of 5-demethoxyubiquinone. Intriguingly, the disruption of the corresponding gene in Caenorhabditis elegans, clk-1, results in a prolonged life span and a slowing of development. Because of the pleiotropic effect of this disruption, the small size of the protein, and the lack of obvious ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
72
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 31 publications
3
72
0
1
Order By: Relevance
“…Although Coq6p and UbiF share 24% sequence identity, it seems unlikely that Coq6p functions like UbiF in the hydroxylation of compound 8 in yeast, because previous studies have shown that yeast Coq7p is required for this hydroxylation step (29). The Coq7 polypeptide has been identified as a di-iron carboxylate protein, a member of a monooxygenase family distinct from UbiF (51). Although E. coli lack a homolog of Coq7p, homologs of yeast Coq7p from other prokaryotic species rescue the E. coli ubiF hydroxylase mutants, indicating that these two distinct types of monooxygenases each catalyze the same reaction in Q biosynthesis (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Coq6p and UbiF share 24% sequence identity, it seems unlikely that Coq6p functions like UbiF in the hydroxylation of compound 8 in yeast, because previous studies have shown that yeast Coq7p is required for this hydroxylation step (29). The Coq7 polypeptide has been identified as a di-iron carboxylate protein, a member of a monooxygenase family distinct from UbiF (51). Although E. coli lack a homolog of Coq7p, homologs of yeast Coq7p from other prokaryotic species rescue the E. coli ubiF hydroxylase mutants, indicating that these two distinct types of monooxygenases each catalyze the same reaction in Q biosynthesis (51).…”
Section: Discussionmentioning
confidence: 99%
“…The Coq7 polypeptide has been identified as a di-iron carboxylate protein, a member of a monooxygenase family distinct from UbiF (51). Although E. coli lack a homolog of Coq7p, homologs of yeast Coq7p from other prokaryotic species rescue the E. coli ubiF hydroxylase mutants, indicating that these two distinct types of monooxygenases each catalyze the same reaction in Q biosynthesis (51). Currently, two of the uncharacterized steps in Q biosynthesis are hydroxylations, and Coq6p may be responsible for either or both of these steps.…”
Section: Discussionmentioning
confidence: 99%
“…clk-1 encodes a highly conserved (3,4) mitochondrial (5,6) protein that is required for ubiquinone (UQ) 1 biosynthesis in yeast (7) and worms (8,9). Recent evidence suggests that CLK-1 is a hydroxylase that converts demethoxyubiquinone (DMQ) into 5-hydroxy-UQ (10). Indeed, a bacterial CLK-1 homologue is capable of replacing the function of UbiFp, the unrelated enzyme that carries out this function in Escherichia coli.…”
mentioning
confidence: 99%
“…In yeast, the COQ7 gene product was found to be responsible for the penultimate step in Q biosynthesis, the hydroxylation of demethoxy-Q (DMQ) to demethyl-Q (7-9). The predicted structure of Coq7p suggests that it is a di-iron carboxylate protein (10). C. elegans with mutations in the clk-1 gene, the COQ7 homologue, show slowed adult behaviors, including defecation cycles and pharyngeal pumping, slowed embryonic and post-embryonic development, and decreased brood sizes (11,12).…”
mentioning
confidence: 99%
“…The polyprenyldiphosphate synthase gene ispB was disrupted, and homologues from different organisms were introduced on plasmids, generating E. coli that produced Q 7 , Q 8 , Q 9 , or Q 10 . We examined the effects of feeding these different Q isoforms on reproductive fitness and progeny viability in both N2 and clk-1 animals.…”
mentioning
confidence: 99%